Invisible but viable: recognising local markets for non-timber forest products - Shackleton, S.; Shanley, P.; Ndoye, O. (2007)
An emphasis on global markets for non-timber forest products (NTFPs) often overshadows attention to the local trade in many traditionally lead to further marginalisation of the low-income groups involved. This paper draws on the literature and the research experience of the authors in three different regions of the world to demonstrate the significance of local markets for NTFPs and to build a case for recognising and strengthening support to them. Discussion includes: features of these markets and current trends favouring them; the benefits they bring to producers and traders; their comparative advantages in relation to their role in strengthening livelihoods; and the policy reforms and development support required to improve them. The authors conclude that a combination of both strong local and export markets permits diversification and choice, assisting poor local people to minimise livelihood risk due to dependence on any single market.